Properties and Uses of Biochars Incorporated into Mortars - Mota-Panizio, Roberta (2023)
Funding Information: The authors would like to acknowledge financial support from the PigWasteBioRefinery Project—Pig biorefinery based on biological, thermal, and electrochemical processes—Demonstrator mobile pilot project, code ALT20-03-0246-FEDER-000054, and co-financed by the European Regional Development Fund (ERDF), through the Regional Operational Program of the Alentejo (ALENTEJO 2020). Publisher Copyright: © 2023 by the authors.